2011
DOI: 10.1002/gj.1299
|View full text |Cite
|
Sign up to set email alerts
|

Zircon U‐Pb/Lu‐Hf and monazite chemical dating of the Tirodi biotite gneiss: implication for latest Palaeoproterozoic to Early Mesoproterozoic orogenesis in the Central Indian Tectonic Zone

Abstract: In this investigation, we reconstruct the latest Palaeoproterozoic to Early Mesoproterozoic orogenic events along the southern margin of the Central Indian Tectonic Zone (CITZ), using sensitive high resolution ion microprobe (SHRIMP) U-Pb zircon dating and Lu-Hf isotope analyses of zircon and Th-U-Pb chemical dating of monazite from samples of the Tirodi biotite gneiss (TBG) unit in the Sausar Mobile Belt (SMB), the latter constituting the southernmost litho-tectonic component of the CITZ. U-Pb zircon dating o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 70 publications
(143 reference statements)
4
61
0
Order By: Relevance
“…11.2). The depleted mantle model age, T DM (Hf), of the juvenile source of the Tirodi gneiss I is c. 3218 Ma (range 3051 -3630 Ma, Bhowmik et al 2011). In this chapter, the older to younger components of the Tirodi gneiss are distinguished by additional roman numerals I -IV.…”
Section: Regional Geology Of the Bastar Cratonmentioning
confidence: 88%
“…11.2). The depleted mantle model age, T DM (Hf), of the juvenile source of the Tirodi gneiss I is c. 3218 Ma (range 3051 -3630 Ma, Bhowmik et al 2011). In this chapter, the older to younger components of the Tirodi gneiss are distinguished by additional roman numerals I -IV.…”
Section: Regional Geology Of the Bastar Cratonmentioning
confidence: 88%
“…The Indian craton is divided into two blocks (the North Indian Block and the South Indian Block) by a prominent orogenic belt (the Satpura Orogen) with wENE-WSW trend in the central part of India. This orogen was earlier considered to be of Grenville (w1000 Ma) age (Bhowmik et al, 1999;Acharyya, 2001;, and was subsequently revised to be of 1600e1500 Ma (Acharyya, 2003;Bhandari et al, 2011;Bhowmik et al, 2011). However, Mohanty (2003Mohanty ( , 2010a has questioned the basis of such an inference, and has shown that this mountain belt had the first orogenic imprint of w2100e1900 Ma and a second event at w1800 Ma.…”
Section: Introductionmentioning
confidence: 86%
“…The earliest of these were developed syn-kinematically with the first deformation of the Sausar Group and have 2100e2200 Ma ages (e.g., 2106 Ma Sm-Nd age for Tirodi Gneiss by Ahmad et al, 2009; 2170 AE 70 Ma Rb-Sr age for the thermal overprint on the Amgaon Gneiss reported by Sarkar et al, 1981 and 2199 AE 178 Ma Rb-Sr age for the Malanjkhand pink granite determined by Panigrahy et al, 1993). The later granites and migmatites have ages between 1618 and 1415 Ma (U-Pb zircon age of 1618 AE 8 Ma reported for Tirodi Gneiss by Bhowmik et al, 2011; 1553 AE 19 Ma U-Pb zircon age for metamorphism of Tirodi Gneiss suggested by Ahmad et al, 2009; 1525 AE 70 Ma Rb-Sr age Barman et al, 1994;C-11: Mallik, 1993; C-12: Rb-Sr WR age Krishna et al, 1996;C-13: Rb-Sr WR age Pandey et al, 1986b;C-14: ID-TIMS monazite ages Chatterjee et al, 2010;C-15: Rb-Sr WR age Pandey et al, 1986a;C-16: Mazumdar, 1996; C-17: U-Pb zircon upper intercept age Sarkar et al, 1998;C-18: ID-TIMS U-Pb zircon upper intercept age Chatterjee et al, 2008;C-19: Rb-Sr WR age Sarkar et al, 1998;C-20: Rb-Sr WR isochron age Dhurandhar et al, 2005Dhurandhar et al, , 2006; C-21: ID-TIMS U-Pb zircon age Chatterjee et al, 2010;C-22: GSI Rec. 125(2), 19-21 (1992); C-23: Pb-Pb WR age Dwivedi et al, 2011;C-24 Sarkar et al, 1986a; 1415 AE 23 Ma monazite overgrowths in Tirodi Gneiss reported by Bhowmik et al, 2011).…”
Section: The Western Domain Of the Satpura Mountainsmentioning
confidence: 93%
“…For example, Ahmad et al (2009) reported a 2056 ± 7 Ma U-Pb zircon age for Tirodi Gneiss; Sarkar et al (1981) determined a 2170 ± 70 Ma Rb-Sr age for the thermal overprint on the Amgaon Gneiss; and Panigrahy et al (1993) reported a 2199 ± 178 Ma Rb-Sr age for the Malanjkhand pink granite. The second group of granites and migmatites developed syn-tectonically with the second deformation of the Sausar Group and have ages between 1618 and 1415 Ma (U-Pb zircon age of 1618 ± 8 Ma reported for Tirodi Gneiss by Bhowmik et al (2011); 1553 ± 19 Ma U-Pb zircon age for metamorphism of Tirodi Gneiss suggested by Ahmad et al (2009); 1525 ± 70 Ma Rb-Sr age determined for Tirodi Gneiss by Sarkar et al (1986); 1415 ± 23 Ma monazite overgrowths in Tirodi Gneiss reported by Bhowmik et al, 2011). The juvenile sources of these later gneisses have a T DM (Hf) age between 2093 and 2523 Ma (Bhowmik et al, 2011) and a T DM (Sm-Nd) age of 2118-2503 Ma ).…”
Section: Stratigraphy and Age Of The Sausar Groupmentioning
confidence: 97%
“…The second group of granites and migmatites developed syn-tectonically with the second deformation of the Sausar Group and have ages between 1618 and 1415 Ma (U-Pb zircon age of 1618 ± 8 Ma reported for Tirodi Gneiss by Bhowmik et al (2011); 1553 ± 19 Ma U-Pb zircon age for metamorphism of Tirodi Gneiss suggested by Ahmad et al (2009); 1525 ± 70 Ma Rb-Sr age determined for Tirodi Gneiss by Sarkar et al (1986); 1415 ± 23 Ma monazite overgrowths in Tirodi Gneiss reported by Bhowmik et al, 2011). The juvenile sources of these later gneisses have a T DM (Hf) age between 2093 and 2523 Ma (Bhowmik et al, 2011) and a T DM (Sm-Nd) age of 2118-2503 Ma ). On the basis of the above geochronological data the deposition of the Sausar Group is inferred to be between 2378 ± 17 and 2200 Ma.…”
Section: Stratigraphy and Age Of The Sausar Groupmentioning
confidence: 97%